Scientific Studies of the Qur’ān in the Contemporary Era: An Analysis of Concept, History, and Methodology - Selamat Amir; Muhamad Alihanafiah Norasid; Ahmad Bazli Ahmad Hilmi (University of Management and Technology (UMT), 2024)
Volume 13 Issue 1